Análise e modelagem de sistema de digestão anaeróbica monitorado para previsão e busca de eficiência de operação - Shubeita, Fauzi de Moraes (2016)
Digesters are devices capable of converting organic waste into biogas and biofertilizer through an Anaerobic Digestion (AD) process. The conceptual simplicity of the equipment hidden the high complexity of chemical and physical processes of AD. This complexity is revealed by the amount of environmental variables that should be monitored to ensure the process efficiency. The primary variables that affect the DA process are temperature, pressure, resulting gas measurement, resulting acids, hydrogen potential (pH) and composition of organic matter. The digesters may be used in urban and rural areas, depending on the type of organic waste. In both places, it is difficult to monitor and control the digesters and therefore compromising their efficiency, which is historically identified as a failure element in projects that have tried to deploy these devices in large scale. In an interdisciplinary way and focusing on the digesters efficiency, we carried out experiments with collection and analysis of biogas and organic waste samples that allowed exploring the microbiological life of a real AD system. This exploration enables us to map the bacteria present in the organic waste, which were classified and grouped according to the four stages of AD (Hydrolysis, Acidogenesis, Acetogenesis, and Methanogenesis). From this analysis, it was possible to develop a mathematical model and software to simulate the behavior of an AD system and a hierarchical control and monitoring model based on a Wireless Sensor Network (WSN). The results of the simulations made it possible to understand and evaluate the behavior of a DA system, especially in temperature control, highlighting how the monitoring and control are essential to production of biogas and biofertilizers.